Analisis Pengalaman Pengguna Pada Aplikasi Ciayo Comic Menggunakan Diary Study Dan User Experience Questionnaire (UEQ) - Resky Ramadhanti; Satrio Hadi Wijoyo; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Entertainment is one of the ways that people do when they are tired when facing their daily activities, including reading comics. With the rapid development of technology, nowadays we no longer need to go to the bookstore to buy comics because we can enjoy online comic through the applications. CIAYO Comics is one of the apps that provides online comics which currently has more than 100,000 users on Google playstore. Based on preliminary observations made on Google Playstore, ciayo comics received poor reviews regarding to the comics' appearance and comics update delay. This affects the user experience and resulting discomfort and dissatisfaction with the user. A good application must provide a sense of comfort when used by its users so that it needs to be analyzed to find user experiences problems and know how well the user experience levels on the application. The user experience measurement is done using the User Experience Questionnaire. Meanwhile, Diary Study is used for the discovery of the problem as well as to explore the experience and in-depth user response and conceptual. From the research results, the UEQ results showed that the average UEQ scale was normal, where all the UEQ scales were in the range -0.8 to 0.8. For the diary study results, 13 problems were found and 5 aspects of the diary study user experience were analyzed in the CIAYO Comics application.